Imagining island food system futures with Indigenous foods: A tok stori on the experiences and potential of traditional food systems in provinces of Solomon Islands - Wate, Jillian Tutuo; Tikai, Pitakia; Lodu, Esther; Vaike, Lyn; Saeni-Oeta, Janet; Bennet, Gregory; Eriksson, Hampus (WorldFish, 2024)
Transition to unhealthy food choices and lifestyles is causing health problems for Solomon Islanders. Due to these circumstances, a tok stori was organized in 2023 to start addressing the following question: “what does a vision for a healthy and safe food system comprise?” (Tutuo et al. 2023). To follow up on these discussions, WorldFish and the Kastom Gaden Association (KGA) organized a second series of forums called Island Food Systems in Transition: Strengthening Indigenous Food Systems in Solomon Islands. The forums were hosted in Gizo, Western Province, on June 13, 2024, and in Buala, Isabel Province, on August 14, 2024 . These forums brought together rural actors and key stakeholders (i) to talk about traditional farming and aquatic foods under a nutrition-sensitive approach and (ii) to listen to ideas about what the future of food systems in Solomon Islands could look like at the provincial level.